Features of the process of energy conversion in differential system of simultaneous generation of the cascade generator - Романюк, В.Є.; Єнчев, С.В. (Proceedings of National Aviation University (archive), 2007)
The electro-kinematics chart of differential synchronous drive-generator aggregate is examined with a cascade generator and its work.